Replication and supercoiling of simian virus 40 DNA in cell extracts from human cells. - Stillman, B W (1985)
Soluble extracts prepared from the nucleus and cytoplasm of human 293 cells are capable of efficient replication and supercoiling of added DNA templates that contain the origin of simian virus 40 replication. Extracts prepared from human HeLa cells are less active than similarly prepared extracts from 293 cells for initiation and elongation of nascent DNA strands. DNA synthesis is dependent on addition of purified simian virus 40 tumor (T) antigen, which is isolated by immunoaffinity chromatography of extracts from cells infected with an adenovirus modified to produce large quantities of this protein. In the presence of T antigen and the cytoplasmic extract, replication initiates at the origin and continues bidirectionally. Initiation is completely dependent on functional origin sequences; a plasmid DNA containing an origin mutation known to affect DNA replication in vivo fails to replicate in vitro. Multiple rounds of DNA synthesis occur, as shown by the appearance of heavy-heavy, bromodeoxyuridine-labeled DNA products. The products of this reaction are resolved, but are relaxed, covalently closed DNA circles. Addition of a nuclear extract during DNA synthesis promotes the negative supercoiling of the replicated DNA molecules.